If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -14g = -3 + -17g Solving 15 + -14g = -3 + -17g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '17g' to each side of the equation. 15 + -14g + 17g = -3 + -17g + 17g Combine like terms: -14g + 17g = 3g 15 + 3g = -3 + -17g + 17g Combine like terms: -17g + 17g = 0 15 + 3g = -3 + 0 15 + 3g = -3 Add '-15' to each side of the equation. 15 + -15 + 3g = -3 + -15 Combine like terms: 15 + -15 = 0 0 + 3g = -3 + -15 3g = -3 + -15 Combine like terms: -3 + -15 = -18 3g = -18 Divide each side by '3'. g = -6 Simplifying g = -6
| 6(3-x)-2(4-x)=0 | | 14x-4=9x+1 | | (4x^2)-4x+1=0 | | 9p+7=10p+10 | | 4x+12=5x+28 | | 4+12=5x+28 | | 3(x-8)+2= | | 3a-7=7a+25 | | (-4x^2)+x+3=0 | | (2x-3)(5-6x)=3x(4x-1) | | 5y=290 | | 3x-10=6x-2 | | 7(x-4)-7=15 | | 9h=55 | | x/(x-16) | | -16=2y-2 | | ln(5.8)=x | | 18/[4x(15-13)-5] | | 5(x+y)=5v+5y | | X+(x*.05)=36.75 | | 3+4x=2x+16 | | -6p-7p=6-8p-8p | | -7a-6a=-7a | | x^2-x-25=5 | | x-5/3=-1/3 | | 7=3z-2 | | -2(7-8n)=-110 | | 7(2x+6)=126 | | 10(1+2k)=490 | | x+1-2=2 | | 7x-3/3x=4 | | X+112+92=180 |